INFLUENCE OF THE METHOD OF LAPAROSCOPIC SUTURING OF PERFORATED PYLORODUODENAL ULCERS ON MOTOR-EVACUATION FUNCTION OF THE STOMACH AND DUODENUM IN EARLY POSTOPERATIVE PERIOD - A. M. Popov; Yu. N. Ul’Yanov; A. V. Lapitskiy; A. M. Antonova (Вестник хирургии имени И.И. Грекова)
The authors researched the influence of different methods of laparoscopic suturing of perforated pyloduodenal ulcers on motor-evacuation function of the stomach and duodenum in 133 patients with peptic ulcer. There were used different methods such as single-row endo-stitch, two-row endo-stitch, omentopexy. The motor-evacuation function of the stomach and duodenum was studied by roentgenocinescopy in the early postoperative period. It was stated, that frequency and intensity of violation of motor-evacuation functions were reliably low in case of imposing the single-row endo-stitch than using the two-row endo-stitch and the omentopexy in the early postoperative period.